2017
DOI: 10.1177/0141076817745711
|View full text |Cite
|
Sign up to set email alerts
|

Politics, scapegoating and mass psychogenic illness: claims of an ‘acoustical attack’ in Cuba are unsound

Abstract: , the United States Department of State announced that it was investigating a mysterious illness cluster among staff working at the American Embassy in Havana, Cuba. The symptoms began in November 2016 and continued in a sporadic fashion through August 2017. In response, several Cuban diplomats working in Washington, DC, were expelled on the grounds that the Castro government had failed in their duty under the Vienna Convention to protect foreign diplomats. 1 The number of those affected eventually reached 24,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Whether the publication of a neuropsychological report clearly below par in a highly respected journal has been dictated by a political agenda we have no means to fathom. Similarly, with limited information it is difficult to postulate alternative accounts of the phenomenon (Bartholomew, 2017). Reports of acoustic attacks are not new, spanning from the Jericho trumpets to the Kokomo Hum.…”
Section: Take Down Policymentioning
confidence: 99%
“…Whether the publication of a neuropsychological report clearly below par in a highly respected journal has been dictated by a political agenda we have no means to fathom. Similarly, with limited information it is difficult to postulate alternative accounts of the phenomenon (Bartholomew, 2017). Reports of acoustic attacks are not new, spanning from the Jericho trumpets to the Kokomo Hum.…”
Section: Take Down Policymentioning
confidence: 99%
“…The onset of a "placebo" type effect is one of the hypotheses that has been suggested in the literature. Among the etiopathogenetic hypotheses most represented in the literature about the symptoms experienced by subjects affected by Havana Syndrome there is that of a mass psychogenic illness that probably originated from the news that circulated about "harmful health attacks" produced by an unknown sound device 13 . 11 .…”
Section: Hypotheses Described In Literaturementioning
confidence: 99%
“…A definite causal link between the series of illnesses indicated in the vicinity of wind turbines and the sound reproduced by them is not described. This has been considered as in favor of a psychogenic hypothesis (Bartholomew, 2017).…”
Section: Hypotheses Described In Literaturementioning
confidence: 99%
“…The onset and persistence of symptoms have occurred in well-circumscribed locations, such as the Hotel Capri and the Hotel Nacional de Cuba, as well as in the homes of U.S. and Canadian diplomats who have reported the appearance of symptoms (Bartholomew, 2017). Double-blind clinical studies have shown that simulated exposure to electromagnetic fields determines in some cases the exact same symptoms reported by subjects affected by a possible Havana Syndrome (Rubin et al, 2006).…”
Section: Hypotheses Described In Literaturementioning
confidence: 99%